An Archive of Feelings : Trauma, Sexuality, and Lesbian Public Cultures - Cvetkovich, Ann, 1957- (Book collections on Project MUSE., 2003)
In this bold new work of cultural criticism, Ann Cvetkovich develops a queer approach to trauma. She argues for the importance of recognizing and archiving accounts of trauma that belong as much to the ordinary and everyday as to the domain of catastrophe. An Archive of Feelings contends that the field of trauma studies, limited by too strict a division between the public and the private, has overlooked the experiences of women and queers. Rejecting the pathologizing understandings of trauma that permeate medical and clinical discourses on the subject, Cvetkovich develops instead a sex-positive approach missing even from most feminist work on trauma. She challenges the field to engage more fully with sexual trauma and the wide range of feelings in its vicinity, including those associated with butch-femme sex and aids activism and caretaking. An Archive of Feelings brings together oral histories from lesbian activists involved in act up/New York; readings of literature by Dorothy Allison, Leslie Feinberg, Cherríe Moraga, and Shani Mootoo; videos by Jean Carlomusto and Pratibha Parmar; and performances by Lisa Kron, Carmelita Tropicana, and the bands Le Tigre and Tribe 8. Cvetkovich reveals how activism, performance, and literature give rise to public cultures that work through trauma and transform the conditions producing it. By looking closely at connections between sexuality, trauma, and the creation of lesbian public cultures, Cvetkovich makes those experiences that have been pushed to the peripheries of trauma culture the defining principles of a new construction of sexual trauma one in which trauma catalyzes the creation of cultural archives and political communities.